2010
DOI: 10.1016/j.ghir.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Body size, IGF and growth hormone polymorphisms, and colorectal adenomas and hyperplastic polyps

Abstract: Objective-We examined the risk of colorectal polyps in relation to body size factors and candidate polymorphisms in selected genes of insulin-like growth factor (IGF1) (rs5742612), IGF1 receptor (IGF1R) (rs2229765), IGF binding protein 3 (IGFBP3) (rs2854746) and growth hormone (GH1) (rs2665802).Design-Cases with colorectal adenomas (n=519), hyperplastic polyps (n=691), or both lesions (n=227), and controls (n=772), aged 20-74 years, were recruited from patients who underwent colonoscopy between December 2004 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…This is similar to at least one other report [25]. However, there are also reports of associations between some of these factors and the presence of hyperplastic polyps [26]–[28].…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to at least one other report [25]. However, there are also reports of associations between some of these factors and the presence of hyperplastic polyps [26]–[28].…”
Section: Discussionsupporting
confidence: 90%
“…Difficulties in measuring an individual's level of physical activity may be a possible explanation. Studies using MET-hours per week showed greater strength of association 42,44 , in comparison to those evaluating categorical variables such as ever v. never physical activity 49,81 .…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Several studies have investigated SP risk in relation to genetic variants linked to the metabolism of the risk factors outlined such as alcohol 87 , smoking 88 ,body fatness 81 and diet 28,54,64 . However, only one study has investigated known CRC mutations -APC, KRAS and MSI interactions with lifestyle factors (namely, smoking status) and SP risk, and found that such mutations were only present in HP patients who smoked, and were not seen in non-smokers 41 .…”
Section: Dietary Factorsmentioning
confidence: 99%
“…We previously showed that elevated fasting insulin levels predicted increased risk of adenomas or colon cancer precursors [4]. Several epidemiologic studies including case-control [5, 6, 7] and cohort studies [8–13] have also evaluated the relationship between colon cancer, IGFs, and factors related to obesity and insulin resistance [14]. While the majority of these studies have reported modest positive associations [1012, 15], other reports have found no associations [9, 11].…”
Section: Introductionmentioning
confidence: 99%